A Poster Digital Sain Media for Humanity Interaction based Interactive Augmented Reality - Muhammad Ashar; Azhar Ahmad Smaragdina; Muhammad Iqbal Akbar; Dicki Dwi Prasetya (Universitas Negeri Malang, 2019)
Interactive and innovative learning media supported by Augmented Reality (AR) is specifically used in the field of science in helping the development of student learning process at State University of Malang (UM). This media is designed to build the pillar of learning innovation strategy through IT fusion on curriculum and learning. Specifically, the main target in the development of teaching media with interaction through AR mobile media and science posters integrated with virtual communications is to improve the visual capabilities of information. Several stages to be done to realize this service are: 1)build a framework of the system in a comprehensive manner, 2)testing with a number of students as a user response, 3)making showcase and 4)demonstrating application system with multimedia content with science materials with 3D perspective (animation and interactive video). The software engineering method used in this application development is the waterfall model, while the qualitative method approach is needed to measure the effectiveness and efficacy of this AR science product on increasing the level of student understanding after using this media through a questioner. It is expected that with the development of this media will accelerate the formation of learning innovation in life-based learning in UM in the future. In broader impact, this work will be able to make UM as a learning innovation university as the competitive and superior university as well as become a reference in the technology of learning media.